POVERTY, FOOD INSECURITY AND CHRONIC DISEASES AMONG FAMILIES: A STUDY OF YAURI LOCAL GOVERNMENT AREA, OF KEBBI STATE - Garba Yauri, Muhammad; Isyaku Muhammad, Suleiman; Abiodun Ayoade, Oladoyinbo (African Journal of Social and Behavioural Sciences, 2024)
This paper examines the reciprocal relationships among poverty, food insecurity and chronic disease among family dynamics as a social variable. This paper explains how chronic illness plays a pivotal role on families, especially individuals with lower socioeconomic status who are affected by different diseases that may lead to immature death. These diseases include chlamydia, genital warts, herpes, gonorrhoea, hepatitis, syphilis, lung cancer and HIV. Some of these diseases can lead to permanent functional disability or even death. The main objective of this study was to examine the reciprocal relationships between chronic diseases among families. The paper adopted triangulation methods of data collection within quantitative and qualitative methods of social science research. The paper has a sample size of 90 respondents from both quantitative and qualitative research. In the qualitative methods, judgemental interviews and key informant interviews (KII) were used to obtain information. The interviewee profile included three nurses, four medical doctors and three members the general population. Relative deprivation theory was used as theoretical framework to explain the issue at hand. The findings of the study revealed that there is a prevalence of hepatitis, HIV and gonorrhoea in the area of the Yauri local government. These findings also indicate that, severe food insecurity among households can cause serious challenges that the members of those houses are at risk of malnourishment and severe hunger and that their children will grow stunted, which can lead to outbreaks of several diseases as the body cannot resist attacked by germs. The study recommended that there be a holistic intervention of public awareness to alert individuals that when they engage in risky behaviours, they may attract several illnesses. In conclusion, the government, healthcare personnel, nongovernmental organizations, and private and public donors, provide good, and adequate medicine that can minimize or reduce certain pain, because it is incurable.